Moral Collapse in a Warming World. Issue 3 (4th September 2014) - Hamilton, Clive
<x content-type="archive" xml:space="preserve">Abstract</x> In his definitive book A Perfect Moral Storm, ethicist Stephen Gardiner argues that the way forward in a climate-changed world is so difficult in part because we "do not yet have a good understanding of many of the ethical issues at stake in global-warming policy." We remain confused about such vital questions as who should take responsibility for the current condition, how to preserve equity between generations, and how best to think about our responsibility toward nonhuman animals. The resistance of governments to taking action, attempts by various players to throw sand in the eyes of the public, and specious arguments used to justify an unwillingness to do what is necessary all add to our moral bafflement.